Penentuan Keberhasilan Involusi Uterus Sapi Perah Friesian Holstein Berdasarkan Kadar Estrogen Setelah Beberapa Penginjeksian Selenium-Vitamin E (DETERMINATION OF THE SUCCESS UTERINE INVOLUTION IN FRIESIAN HOLSTEIN DAIRY COW BASED ESTROGEN LEVELS AFTER MU - Prasdini, Widya Ayu; Rahayu, Sri; Djati, Mochammad Sasmito (Jurnal Veteriner, 2015)
The aims of this study were to determine the effectiveness of selenium-vitamin ETM to the increasedlevels of estrogen as a sign of completion uterine involution process in dairy cows Frisian Holstein (FH)after calving. Twenty pragnant FH cows were used in this experiment. The cows devided into four groups.The first group (as control, P0) was not given selenium-vitamin ETM, the second group (P1) was given 0.5mg/mL selenium + 50 mg/mL vitamin ETM, the third group (P2) was given 1,5 mg/mL selenium + 50 mg/mLvitamin ETM and the fourth group (P3) was given 2 mg/mL selenium + 100 mg/mL vitamin ETM. Theadministration of selenium-vitamin ETM performed at the 7th months of pragnancy, 8th month of pragnancy,two weeks before calving, 7 and 14 days after calving intramuscularly. After calving, the serum of dairycows were taken for analysis of estrogen levels on the 25th day, the 45th, the 65th and current first postpartumestrus in the position of standing heat using Bovine Estrogen ELISA Kit (EST) methode . The results of theanalysis of high estrogen levels on day 25, the 45th, the 65th and current first estrus days after giving birthin units of pg / mL found in treatment 3 (P3), which were a 8.94 ± 0.22; 9.64 ± 0.55; 9.86 ± 0.67and 10.14 ±0.84 respectively, but the fastest uterine involution based estrogen levels was in treatment 2 (P2) on the45th day with 9.12 ± 0.94 for the estrogen levels.. The conclusions of the study was the addition of seleniumand vitamin E at the 7th month of pragnancy until the 14th day after calving may significantly affecton theincreased levels of estrogen which indicates the success of uterine involution in dairy cows FH.
Keywords: selenium-vitamin ETM, estrogen levels, involution uterine